Respuesta :

Answer:

See below.

Step-by-step explanation:

1. f(x) = x - 3

we need to calculate [ f(x + Δx) - f(x)]  / Δx

(Δx means a small quantity of x)

For x - 3 we substitute f(x) with x - 3 in the above formula and for f(x +Δx) we substitute  x + Δx - 3:-

( x + Δx - 3)  - (x - 3) /   Δx

=  (x - x - 3 + 3 +  Δx) /  Δx

=  Δx /  Δx

= 1.

2.  x^2 - 2, we have

[(x +  Δx)^2 - 2 - (x^2 - 2)]  /   Δx

(x^2 + 2x Δx +  (Δx)^2  - 2 - x^2 + 2) /   Δx

=   2xΔx + ( Δx)^2 /   Δx

= 2x + Δx.

The others are evaluated n the same way.i

ACCESS MORE